An investigation on a triple material double gate cylindrical gate all around (TMDG-CGAA) MOSFET for enhanced device performance. (2020) - Menaria, Asmita; Pandey, Rahul; Kumar, Ramesh
Abstract: The present work investigates the Triple Material Double Gate Cylindrical Gate All Around (TMDG-CGAA) MOSFET in the nanometer regime to improve the device performance. Electrical parameters of TMDG-CGAA MOSFET are investigated under varying physical conditions like channel length, channel thickness, oxide thickness, and core diameter. For various parameters like drain current, threshold voltage, DIBL, and transconductance the TMDG-CGAA MOSFETs are evaluated. The comparison has been done among the SG-CGAA MOSFET, DG-CGAA MOSFET, and TMDG-CGAA MOSFET by using the same device parameters. The proposed structure TMDG-CGAA MOSFET has been validated by a device simulator named as 3D ATLAS tool. The device performance enhances by incorporating three materials at the gate electrode in the DG-CGAA MOSFET. In the planar MOSFET devices the SCEs enhances and also the threshold voltage is rolling off due to the reduced potential barrier between source and drain. But in the proposed structure the threshold voltage increases in the nanometer region also due to its cylindrical geometry. The drain current, transconductance also improves in comparison with the SG-CGAA MOSFET and DG-CGAA MOSFET. The SCE like DIBL decreases in the proposed structure. So overall the proposed structure shows better device performance with fast switching and lower cost.